Regularizing cubic open Neveu-Schwarz string field theory - Berkovits, Nathan [UNESP]; Siegel, Warren (Springer, 2009)
After introducing non-minimal variables, the midpoint insertion of Y (Y) over bar in cubic open Neveu-Schwarz string field theory can be replaced with an operator N(rho) depending on a constant parameter rho. As in cubic open superstring field theory using the pure spinor formalism, the operator N(rho) is invertible and is equal to 1 up to a BRST-trivial quantity. So unlike the linearized equation of motion Y (Y) over bar QV = 0 which requires truncation of the Hilbert space in order to imply QV = 0, the linearized equation N(rho)QV = 0 directly implies QV = 0.
Keywords: Superstrings and Heterotic Strings; String Field Theory